The Integration Of Aesthetic And Ethic In Islamic Education: Building Harmony Among Knowledge, Values, And Beauty - Aas Sholichah; Muhamad Wijaksono; B. Syafuri B. Syafuri; Soesari Soesari (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2026)
This study aims to examine the integration of aesthetics and ethics in Islamic education as an effort to build harmony between knowledge, values, and beauty. The background of this study is based on the phenomenon of modern education which tends to emphasize cognitive and pragmatic aspects, thus ignoring the moral and aesthetic dimensions in the learning process. In fact, from an Islamic perspective, aesthetics (al-jamāl) and ethics (al-akhlāq) are two important aspects that are interrelated in forming a complete and civilized human being. This study uses a qualitative method with a descriptive-analytical approach, as well as a philosophical and pedagogical approach. Data collection techniques are carried out through literature studies by reviewing various relevant primary and secondary sources, such as books, scientific journals, and the works of Western and Islamic educational figures. The data analysis techniques use content analysis and descriptive-critical analysis to identify, interpret, and construct the concept of the integration of aesthetics and ethics in Islamic education comprehensively. The results of the study indicate that aesthetics in Islamic education plays a role in creating a harmonious, inspiring learning atmosphere and touching the emotional aspects of students, while ethics serves as a moral foundation in shaping character and behavior in accordance with Islamic values. Integrating the two is crucial for creating holistic learning, oriented not only toward mastery of knowledge but also toward the development of morals and a sensitivity to beauty. This principle of integration can be implemented through the curriculum, learning methods, and the role models of educators.